Insights into the Biological Evaluation of Pterocarpanquinones and Carbapterocarpans with Anti-tumor Activity against MDR Leukemias - Rumjanek, Vivian M.; Maia, Raquel C.; Salustiano, Eduardo J.; Costa, Paulo R.R. (Anti-Cancer Agents in Medicinal Chemistry, 2019)
In an attempt to find anticancer agents that could overcome multidrug resistance (MDR), two new classes of modified isoflavonoids were designed and synthesized, and their effectiveness evaluated against a vast array of tumor cell lines. Pterocarpanquinone (LQB-118) and 11a-aza-5-carbapterocarpan (LQB-223) were the most promising. LQB-118 induced cell death, in vitro, in the μM range, to a number of human cancer cell lines as well as to fresh tumor cells obtained from patients with acute or chronic myeloid leukemia, independent on whether they exhibit the MDR phenotype or not. Furthermore, leukemic cells were more sensitive to LQB- 118 compared to cells from solid tumors. Given to mice, in vivo, LQB-118 affected the growth of melanoma, Ehrlich carcinoma and prostate cancer cells. Conversely, no general toxicity was observed in vivo, by biochemical, hematological, anatomical or histological parameters and toxicity in vitro against normal cells was low. The process involved in tumor cell death seemed to vary according to cell type. Apoptosis was studied by externalization of phosphatidylserine, DNA fragmentation, caspase-3 activation, reduced expression of XIAP and survivin, ER stress, cytosolic calcium increase and mitochondrial membrane depolarization. Autophagy was also evaluated inhibiting caspase-9, with no effect observed in beclin 1, whereas pre-treatment with rapamycin increased cytotoxicity induced by LQB-118. In addition, LQB-118 increased ROS, inhibited NFΚB nuclear translocation and secretion of TNF-α, modulated microRNAs miR-9 and miR-21 and modified the cell cycle. Despite being less studied, the cytotoxic effect of the 11a-aza-5-carbapterocarpan LQB-223 was present against several tumor cell lines, including those with the MDR phenotype.
Keywords: anticancer agents